ANALISIS EDUKASI GIZI, PENGETAHUAN, POLA MAKAN DAN STATUS GIZI PADA PASIEN DIABETES MELITUS RAWAT JALAN DI RSUD IBNU SINA KABUPATEN GRESIK - Mamluatur Rohmah Agustina; Dian Agnesia; Heri Purnama Pribadi (Universitas Muhammadiyah Gresik, 2021)
Diabetes mellitus is a symptom that arises in a person due to an increased in blood sugar (blood glucose) levels. One of the management for diabetes mellitus patient is by providing education through nutritional conseling on various problems related to diabetes mellitus to increased knowledge. The purpose of this research to analyzed nutrions education of knowledge, dietary habit and nutritional status in diabetes patients at ibnu sina gresik general hospital. The method used was pre-experimental with one-group pretest and posttest with 1 observationed in 5-10 minutes. The data collection technique using a questionnaire and through interviews with subjects and the analyzed using pearson correlation and paired samples test. The subjects using outpatient Diabetes Mellitus patients who were taked by accidental sampling according to the inclusion and exclusion criteria, as many as 40 people. The results of the pearson correlation there was a not correlation between knowledge and nutritional status (P value= 0,063), there was a correlation between knowledge and dietary habit (P value= 0,000), there was a correlation between dietary habit and nutritional status (P value= 0,028) and the result of the paired t-test there was a difference between before and after being gived nutrition education with the mean±SD knowledge of subjects before and after namely 1,08±0,267 and 2,13±0,335 with a value of p = 0,000 or <0,05.